Optimal reactive power control for 3-phase EMT SVC grid-connected converter - Kouki, Mohamed; Trajin, Baptiste; Vidal, Paul-Etienne (2024 IEEE PES Innovative Smart Grid Technologies Europe (ISGT EUROPE), 2024)
Nowadays, the integration of power electronics into power systems has increased significantly. As a result, power grids were subject to numerous transformations. Hence, operations, power factor corrections, and voltage control of the grid-connected converters have become challenging tasks subject to enhancing the stability, reliability, and performance of the power grid. For this, we propose in this paper an advanced state-feedback control using the linear quadratic regulator (LQR) optimized by the metaheuristic method for a 2-level 3-phase voltage source converter (VSC) connected to the utility grid through an output L-type or LCL-type filter. The proposed methodology avoids the empirical trial-and-error technique for adjusting the weighting values of matrices Q and R respecting multi-objectives: (i) minimize control loop errors, (ii) minimize the overshoot, and (iii) respect suitable time constant. Thus, the optimal weighting matrices are provided using the multi-objectives Tunicate Swarm Algorithm-TSA. The effectiveness of the proposed methodology is tested on Electromagnetic Transients (EMT) VSC grid-connected systems and compared to standard vector control and advanced control (H ∞ ). The proposed methodology permits important performance regulation of reactive power for the feasible VSC operation range and under perturbation conditions (short circuits,...).